The Effect Of Service Quality On Consumer Satisfaction At Umkm Bengkel Lestari Temas Batu - Asep Dana Saputra; Sudarmiatin, Sudarmiatin; Wening Patmi Rahayu (Cita konsultindo, 2024)
The success of car service implementation is largely determined by the service's ability to meet customer needs and solve problems quickly, accurately, and anywhere. The main focus of automotive companies is the orientation towards customer satisfaction in order to win the increasingly tight competition. In this case, UMKM Bengkel Lestari Temas Batu strives to provide the best service quality through three main dimensions: interaction quality, physical environment quality, and result quality. Interaction quality includes the attitude, behavior, and expertise of service providers, especially in terms of sales, repairs, availability of spare parts, and body repair. Physical environment quality involves ambient conditions, design, and socialization of services that support customer satisfaction. Meanwhile, result quality refers to fast and satisfying service without causing complaints from customers. UMKM Bengkel Lestari Temas Batu strives to improve these three aspects, as reflected in the increasing number of customers using Suzuki cars. Therefore, this study aims to analyze the effect of service quality on customer satisfaction at Bengkel Lestari Temas Batu. The results of this study are expected to provide deeper insight into strategies for improving service quality in order to maintain customer loyalty.